Necesidad de reformar el art. 188 del codigo laboral el cual vulnera el derecho de los trabajadores establecido y garatizado en la constitucion de la república del Ecuador. - Pincha Pallo, Jose Mauricio (2015)
The Social Law, is one of the most important goals of social policy, which in this work is immersed regime, labor regulation in the State as well as the leadership of the working policy in general which rests on productive activity and the development of the nation, in whose regime say virtually the legal principles of personality, for which social arrangements which are made important achievements of modern labor law that make labor law continuously prescribe an true Labor Code. Justified the labor regime, I believe that is the result of a young discipline, which found in full training, present difficulties even for designation, resulting vague and generic and even somewhat technical, the reasons for this could manifest itself consideration of the nature of the legislation, because being this right tending to social justice, it seems logical that this denominació scope of labor law, that is closely related to the so-called social question, which is historically linked doctrinal; because even though you have every right in a sense, a social meaning, this one has a more special way, as a reaction against individualistic systems, because it contains a larger content than other denominations, not in the sense that their use is justified more understand because larger number of subjects, but because, given the wide range of these, and of people to be covered. Labor law, known as Labour regime arises in Ecuador, with the statement of the result of the convergence of national and international factors, and whose object is focused on the establishment of the legal, social, and economic equity, and is not but may be made on the basis of social justice. Labor law as a set of principles, norms and institutions that protect, tend to dignify and vindicate those who live their material or intellectual efforts for the realization of its historical destiny, as human life is socializing. Rights at work are at the core in the labor-management relationship. Work through the story is considered crucial point in the development of large enterprises or public or private institutions run by economic entities such as the state or employers.